In vitro translation of adenovirus type 12-specific mRNA isolated from infected and transformed cells. - Esche, H (1979)
The early and late gene products of human adenovirus type 12 (Ad12), as well as the viral proteins synthesized in an Ad12-transformed cell line, were identified by translation of viral mRNA in an in vitro protein-synthesizing system. Cytoplasmic RNA was isolated from permissive KB or nonpermissive BHK cells infected with Ad12 and from Ad12-transformed HA12/7 cells. Virus-specific RNA was selected by hybridization to Ad12 DNA covalently bound to cellulose. Viral RNA was then translated in a fractionated rabbit reticulocyte cell-free system or in wheat germ S-30 extracts. The proteins synthesized were characterized by immunoprecipitation and subsequent electrophoresis on sodium dodecyl sulfate-polyacrylamide gels. RNA prepared from KB cells late after infection with Ad12 elicited the synthesis of most of the structural polypeptides of the virion and at least two presumably nonstructural Ad12 proteins. When viral RNA isolated early after infection of KB cells with Ad12 was translated in vitro, 10 polypeptides were observed: E-68K, E-50K, E-42K, E-39K, E-34K, E-21K, E-19K, E-13K, E-12K, and E-10K. Ad12-specific RNA was also isolated from the Ad12-transformed hamster cell line HA12/7, which contains several copies of the Ad12 genome integrated in the host genome. The RNA codes for at least seven polypeptides with molecular weights very similar to those of the early viral proteins.